Suppressing the Financing of Terrorism : A Handbook for Legislative Drafting. (Manuals and Guides, 2003)
In recent years, the IMF has become deeply involved in the international movement to prevent the abuse of financial systems and to protect and enhance the integrity of the international financial system. The IMF's involvement has been expanded beyond anti-money-laundering efforts to include those aimed at combating the financing of terrorism. This handbook will facilitate the provision of relevant technical assistance by providing a compendium of essential materials for officials drafting legislation designed to combat such financing. The relevant international standards and obligations are presented, together with examples of existing legislation designed to meet them. The issues discussed in this book are relevant to all countries, regardless of their individual geopolitical situations.